Potato Physiological Disorders – Internal Heat Necrosis - Lincoln Zotarelli; Christine M. Worthington; Chad M. Hutchinson; Seth Byrd; Douglas Gergela; Diane Rowland (EDIS)
Internal heat necrosis is a physiological disorder that causes an unacceptable browning of the tuber tissue and can cause economic losses to the grower. The three leading suspected causes of IHN in tubers are high soil temperature, inadequate soil moisture, and suboptimal plant nutrition, or a combination of these factors. This revised 3-page fact sheet was written by Lincoln Zotarelli, Christine M. Worthington, Chad M. Hutchinson, Seth Byrd, Douglas Gergela, and Diane Rowland, and published by the UF Department of Horticultural Sciences, July 2012.